Economic Growth and Stanadard of Living - Hovsepyan, Volodya (Bulletin of Yerevan University G: Economics, 2014)
Economic growth is the main indicator of social and economic development. At the same time, it is the unique indicator of economic activities of the government, a guarantee of economic security and independence. Despite the fact, that, according to the statistics, the Republic of Armenia experiences high rates of economic growth, the standart of living of the population does not grow proportionally. From this perspective, the acticle describes the main causes mentioned above, and suggests ways of improving the living standards of the population.
Keywords: economic growth, economic development, rates of economic growth, gross national product, the welfare of society, quality of life, standard of living of the population